English as a Pivot Language in Audiovisual Translation: Industry and Profession in Spain - Carrero Martín, José Fernando; Reverter Oliver, Beatriz (Íkala, Revista de Lenguaje y Cultura, 2023)
Audiovisual translation has undergone a revolution in the last decade, with an increase in the number of non-English speaking productions. This has increasingly turned English into a pivot language. This article presents a mixed study aiming to profile translators who work with English as a pivot language. It describes the characteristics of assignments in language combinations involving English as a pivot language. In addition, translators’ experiences and opinions on this practice are collected. Data collection was carried out by means of a questionnaire and personal interviews with professionals who have dealt with assignments of this nature. The results show that this practice has increased in the last five years due to the expansion of video on demand. Even so, this type of assignment accounts for less than 10% of the workload of the translators surveyed. Moreover, this practice is used with both common and exotic languages in the Spanish AVT market. Translators recognise that this is not a deontologically ideal practice, but it enables the reception of products that would otherwise be unavailable in Spain.